Resisting orthodoxy in a highly distorted economy: economic policy in Peru - Federico Foders (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1987)
Peru belongs to the club of Latin American countries which recently declined to follow "orthodox" adjustment programmes and implemented a "heterodox" policy package instead. The orthodox approach involves stabilisation by drastic budget cuts and monetary discipline, liberalisation of factor markets and the trade regime, whereas heterodox policies include strict price controls on factor and goods markets, an expansionary monetary policy, import protection and multiple exchange rates. Further, while orthodox measures entail a shock therapy, heterodox measures are associated with a gradualist approach. This paper analyses the rationale for an heterodox medicine in the Peruvian case. First, the performance of the Peruvian economy in 1970 - 1985 is studied in an attempt to arrive at a diagnosis of the central disease affecting economic policy in Peru. The conclusion is that the mix of monetary, fiscal and exchange rate policies chosen was inconsistent and that this inconsistency seems to have contributed to serious imbalances at both the macro- and microeconomic levels. The inward-oriented industrialisation strategy followed by this country offered the appropriate background for the development of this inconsistency. This result, along with a critical review of the economic consequences of the Peruvian Government's heterodox plan, leads to the conclusion that this country could reap significant welfare gains from a reform of the policy regime in the direction of orthodox adjustment measures and a stronger world-market orientation.
Keywords: 330; Wirtschaftspolitik; Peru